(untitled) (KULT_online, 2014)
In many conventional portrayals the Khrushchev era (1953-1964) is depicted as a period of the successful arousal of a spirit of optimism within soviet society through liberal political reforms. Often the term ’thaw’ illustrates such perceptions, but it also reflects the impressions of many contemporaries. While Robert Hornsby analyses the arbitrary reactions of the regime concerning all possible forms of individually prosecutable behavior, which included examinations of the personal motives of the protagonists, he challenges such stereotypes in an inspiring manner. Beyond that this book indicates important developments in the history of the Soviet Union after Stalin.